Differential expression of Spiroplasma citri surface protein genes in the plant and insect hosts. Issue 1 (December 2016) - Dubrana, Marie-Pierre; Béven, Laure; Arricau-Bouvery, Nathalie; Duret, Sybille; Claverol, Stéphane; Renaudin, Joël; Saillard, Colette
Abstract Background Spiroplasma citri is a cell wall-less, plant pathogenic bacteria that colonizes two distinct hosts, the leafhopper vector and the host plant. Given the absence of a cell wall, surface proteins including lipoproteins and transmembrane polypeptides are expected to play key roles in spiroplasma/host interactions. Important functions in spiroplasma/insect interactions have been shown for a few surface proteins such as the major lipoprotein spiralin, the transmembraneS. citri adhesion-related proteins (ScARPs) and the sugar transporter subunit Sc76.S. citri efficient transmission from the insect to the plant is expected to rely on its ability to adapt to the different environments and more specifically to regulate the expression of genes encoding surface-exposed proteins. Results Genes encodingS. citri lipoproteins and ScARPs were investigated for their expression level in axenic medium, in the leafhopper vectorCirculifer haematoceps and in the host plant (periwinkleCatharanthus roseus ) either insect-infected or graft-inoculated. The vast majority of the lipoprotein genes tested (25/28) differentially responded to the various host environments. Considering their relative expression levels in the different environments, the possible involvement of the targeted genes in spiroplasma host adaptation was discussed. In addition, twoS. citri strains differing notably in their ability to express adhesin ScARP2b and pyruvate dehydrogenase E1 component differed in their capacity to multiply in the two hosts, the plant and the leafhopper vector. Conclusions This study provided us with a list of genes differentially expressed in the different hosts, leading to the identification of factors that are thought to be involved in the process ofS. citri host adaptation. The identification of such factors is a key step for further understanding ofS. citri pathogenesis. Moreover the present work highlights the high capacity ofS. citri in tightly regulating the expression level of a large set of surface protein genes, despite the small size of its genome.